Effects of external magnetic field and out-of-plane strain on magneto-optical Kerr spectra in CrI3 monolayer. (20th June 2018) - Guo, Guanxing; Bi, Gang; Cai, Chunfeng; Wu, Huizhen
Abstract: Magnetic semiconductors based on two-dimensional (2D) crystals have attracted attention owing to their intrinsic ferromagnetism and have potential for spintronic devices. Here, full-potential linearized augmented plane wave plus local orbitals method is used to explore the structural, electronic, magnetic, and magneto-optical properties of CrI3 monolayer. Our first-principles calculations show that CrI3 monolayer is a ferromagnetic indirect semiconductor with spin-up and spin-down band gaps of 1.23 and 1.90 eV, respectively, and a magnetic moment of 2.93 per Cr atom. Based on the macroscopic linear response theory, we systematically study the influences of external magnetic field and out-of-plane strain on the magneto-optical Kerr effect spectra in CrI3 monolayer. The Kerr rotation of CrI3 monolayer at 1.96 eV photon energy is, which is consistent with the recent experiments. We find that the Kerr rotation reaches its maximum when the external magnetic field is perpendicular to CrI3 plane, while it is almost zero on turning the magnetic field in the plane. This result as well as the sizable magnetocrystalline anisotropy energy (MAE) of 0.79 meV verifies that CrI3 monolayer has a strong magnetic anisotropy with an out-of-plane easy axis. Further, applying out-of-plane compressive and tensile strain upon CrI3 monolayer, we observe a redshift of the Kerr rotation spectra with the increase of the strain and the peak values of the Kerr rotation increase correspondingly. The rich electronic and magnetic properties, especially the magneto-optical spectra, render CrI3 monolayer a promising 2D magnetic material for applications from sensing to data storage.